Immunostimulatory Activity of Apios Tuber Extract on RAW264.7 Macrophage Cells - Cui, Jun; Kim, Yosup; Lee, Eun Byul; Kim, Jong-Keun; Kang, Tae-Hoon; Jang, Ho Hee (Journal of bacteriology and virology, 2016)
Apios americana Medik tubers are medicinal foods with anti-cancer and anti-inflammatory activities. However, mechanisms of immunostimulatory action of the Apios tuber extract (ATE) on macrophages have not been elucidated. In the present study, we investigated whether ATE could modulate immune responses, such as production of nitric oxide (NO), proinflammatory cytokines, and transcription factors, in RAW264.7 macrophage cells. ATE significantly increased the production of NO and proinflammatory cytokines such as $interleukin-1β$ ($IL-1β$), IL-6, and tumor necrosis $factor-α$ ($TNF-α$), and induced the mRNA and protein levels of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) and proinflammatory cytokines in a dose-dependent manner. Furthermore, Western blot analysis revealed that ATE activated the transcription factor Nuclear $Factor-κB$ and mitogen-activated protein kinases signaling cascades, including extracellular signal-regulated kinase, c-Jun N-terminal kinase, and p38 kinase. In addition, we found that ATE induced the activation of macrophages through upregulation of toll-like receptor 4 (TLR4) and TLR2. Taken together, these findings indicate that ATE possesses a potential as a functional food with immunostimulatory activity.